The semiology of ’Habib Bourguiba’ statue: في صيد العلامة: سيميولجيا تمثال "الحبيب بورقيبة" التّونسي - Imen abdellatif Sakly (Journal of engineering sciences and information technology, 2021)
The search for the sign presupposes the fact of being skilled enough to understand the semiotic mechanisms having a deep grasp of the field of semiology. In fact, it is a virtuosity that may be overlooked by a common citizen as it may surpass his cognitive abilities and capabilities in several cases, given that by nature he is unable to process the technical terms necessary to explain what is taking place around him or to express its connotations in a proper way. However, despite this fact, a common citizen may be able to read some of the covert or encrypted messages that are usually drawn from his daily surroundings and the variety of its topics, without being able to professionally dismantle its epistemological connotations and reconstruct them logically and systematically. Whereas, what is striking about the matter is that we- as intellectuals- come to convey this reality to the citizen himself through scientific methods even if they are pre- and post- objective techniques as it inevitably differs from the common way of thinking we are used to, in an attempt to shed light on the aspects that have fallen short or deficient in terms of analysis and interpretation, hoping that we would be able to regroup its dispersed signs, or at least figure out its processes and essences without distortion or falsification. Therefore, we resorted to the use of this article to highlight the importance of ‘Habib Bourguiba’’s statue as a model to study the signs’ life and dynamics, to examine the extent to which the artist is aware as well as the limits of his alienation. Throughout this artistic effect, we also want; to take a closer look at some of the Tunisian society’s issues, almost thought we have given up scrutinizing its details. These details seem to resurface each time this artistic work manifested itself throughout the different styles of its political transformations.